Effect of Solvents on the Fluorescent Spectroscopy of BODIPY-520 Derivative - Kamel, Buthaina; Sayem El-Daher, Moustafa; Bachir, Wesam; Ibrahim, Amina; Aljalali, Sinan (Journal of Spectroscopy, 2022)
Photodynamic therapy (PDT) is a selective and minimally invasive technique for the treatment of tumors. It includes three components such as photosensitizer, light, and molecular oxygen. The purpose of this work is to investigate the effect of the solvents such as methanol, ethanol, acetone, and water on fluorescent spectroscopy produced by one of the BODIPY derivatives in turbid media. A 520 nm laser diode is used for exciting one of the BODIPY derivatives as a photosensitizer in tissue-like optical phantoms. Results show that the photosensitizer studied without absorption and scattering components in the methanol and ethanol solvent has a prominent fluorescence peak at 600 nm, whereas acetone solvent has a prominent fluorescence peak at 546 nm. Experimental results reveal that when absorption and scattering components are present in addition to the studied solvents, the characteristic fluorescence intensity peak is red-shifted to 678 nm.